Role of laparoscopy in the management of impalpable testis in children: a study in Bangladesh - Huque, Muhammad Moinul; Hannan, Md Jafrul; Hasina, Kaniz; Ul Huq, Ashraf (Bangladesh Journal of Endosurgery, 2013)
Introduction: Treatment of the cryptorchid testicle is justified due to the increased risk of infertility and malignancy as well as the risk of testicular trauma and psychological stigma on patients and their parents. Approximately 20% of cryptorchid testicles are impalpable. In these cases, the laparoscopic technique is the method of choice for diagnosis and treatment. Materials and Methods: From 1 April 2009 to 31 October 2010, 37 testicles of 30 patients were submitted to diagnostic laparoscopy for impalpable testes. This was a prospective study seeking the diagnostic accuracy and therapeutic outcomes of use of laparoscopy in impalpable testes. Age, operative techniques, complications, the cosmetic aspect and outcomes were also recorded. Results: Mean age was 6.64 ± 3.96 years and 23% cases were bilateral. Twenty-one cases had primary orchiopexy, 9 had 1st stage Fowler- Stephens (FS) procedure, 3 had 2nd stage FS, 13 cases needed inguinal exploration and there was one vanishing testicles. Average operating time was 40 min for diagnostic laparoscopy, 90 min for unilateral and 120 min for the bilateral cases. Two of the patients had late postoperative complications e.g. one uretereral obstruction and one recurrence. Conclusions: In pediatric age group, the laparoscopic approach is safe and feasible. The purpose of study is to see whether the laparoscopic procedure presents excellent results in terms of diagnosis and therapy of the impalpable testis. DOI: http://dx.doi.org/10.11593/bje.2013.0101.0005 Bangladesh Journal of Endosurgery Vol.1(1) January 2013: 16-20